Advances in cryopreservation of Syzygium maire (swamp maire, maire tawake) zygotic embryos, a critically endangered tree species endemic to New Zealand - van der Walt, Karin; Nadarajan, Jayanthi; Mathew, Liya; Bettoni, Jean C.; Souza, Juliana A. (Frontiers in Conservation Science, 2023)
Syzygium maire is a threatened Myrtaceae tree species endemic to New Zealand. Due to its highly recalcitrant seed, cryopreservation is the only viable long-term ex situ conservation option for this species. Our previous attempts to cryopreserve the embryonic axis (EAs) of this species S. maire were unsuccessful but did provide a better understanding of desiccation behaviour, biochemical composition, oxidative status, and ultrastructural changes associated with desiccation in EAs. We incorporated this knowledge with biophysical information to investigate two advanced cryopreservation technologies: a droplet vacuum infiltration vitrification (DVIV) method and a novel metal-mesh vacuum infiltration vitrification (MVIV) method using Plant Vitrification Solution 2 (PVS2) for cryopreservation of the EAs. The PVS2 treatment at room temperature (~20°C) proved phytotoxic with extended PVS2 incubation significantly reducing EA survival. No EAs survived cryopreservation using DVIV, however MVIV resulted in post-cryopreservation survival of up to 19% following PVS2 incubation for 20 min. Biophysical thermal analysis using Differential Scanning Calorimetry revealed a 15-fold reduction in ice crystallization following incubation in PVS2 for 20 min or more, with all freezable water removed after 60 min incubation. These results present a significant advance in being able to successfully cryopreserve S. maire EAs. The findings from this study will aid the development of cryopreservation protocols for other extremely recalcitrant seeded species, many of which are threatened with extinction due to climate change, plant pathogens attack, and habitat destruction.